Pengaruh Work-Life Balance dan Motivasi Kerja terhadap Kinerja Pegawai pada Bagian Marketing Bank Bri Kantor Cabang Cimahi - Khoirunnisa, Hanifah; M.Vrans Romi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of work-life balance and work motivation on employee performance in the marketing department of Bank BRI Cimahi Branch Office. Work-life balance is an important factor in maintaining a balance between personal life and work, which has a direct impact on employee productivity and well-being. In addition, work motivation plays a crucial role in determining individual performance in carrying out their duties. The research method used is quantitative with a positivism approach, where data is collected through questionnaires distributed to 35 marketing employees using a saturated sample technique. Data analysis was carried out with validity, reliability, multiple linear regression, and hypothesis testing to measure the relationship between the independent and dependent variables. The results showed that work-life balance and work motivation have a positive and significant influence on employee performance. Employees with good work-life balance and high motivation levels are more productive and have better job satisfaction levels. Therefore, companies are advised to increase work flexibility, provide incentives, and create a conducive work environment to support employee welfare. Keywords: Work Flexibility, Employee Performance, Work Motivation, Productivity